Marketing Tactics and Corporate Image: The Key to Maintaining Loyalty - Pahmi Pahmi; Tasrim Tasrim; Ansri Jayanti; Satria Lintang Rachmadana; Munzir Munzir (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2023)
The banking sector is a business that really needs attention regarding retaining customers because this sector generally offers relatively the same type of service. This research aims to analyze marketing tactics consisting of service quality, service convenience, and added value to loyalty—corporate image variable as a mediating variable. The research population is customers of Sharia commercial banks in Indonesia. The research sample was 360 customers. SEM PLS was used for data analysis with the help of warpPLS 7.0. The results showed that marketing tactics and company image are determinants in increasing customer loyalty. Service quality, convenience services, and added value can be part of marketing tactics to increase loyalty. Meanwhile, the company image did not succeed in providing a mediating effect from marketing tactics with loyalty because companies generally only see the image partially. The results contribute to economic utility theory, showing that utility provides a reciprocal effect between banks and customers.